2022
DOI: 10.3390/cells11020249
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Molecular Targeting of Colon Cancer to Visualize the Invisible

Abstract: Colorectal cancer (CRC) is a common cause of cancer and cancer-related death. Surgery is the only curative modality. Fluorescence-enhanced visualization of CRC with targeted fluorescent probes that can delineate boundaries and target tumor-specific biomarkers can increase rates of curative resection. Approaches to enhancing visualization of the tumor-to-normal tissue interface are active areas of investigation. Nonspecific dyes are the most-used approach, but tumor-specific targeting agents are progressing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 170 publications
(181 reference statements)
0
11
0
Order By: Relevance
“…Lieto [55] found that the diagnostic performance of ICG-FI was significantly superior to that of both preoperative (p = 0.027) and intraoperative (p = 0.042) conventional procedures, indicating that intraoperative ICG-FI may enhance patient outcomes after CS for PC due to CRC. A study by Lwin [56] reported fluorescence-associated molecular biomarkers in preclinical and clinical assessments. Numerous fluorescently tagged antibodies, peptides, particles, and other compounds relevant to cancer hallmarks have been produced for the lighting of the target lesion, as underlined by Mieog [57], Privitera [58], Nagaya [59] and Tipirneni [60].…”
Section: Improving the Detection Of Cancer Tissue And Targeted Treatmentmentioning
confidence: 99%
“…Lieto [55] found that the diagnostic performance of ICG-FI was significantly superior to that of both preoperative (p = 0.027) and intraoperative (p = 0.042) conventional procedures, indicating that intraoperative ICG-FI may enhance patient outcomes after CS for PC due to CRC. A study by Lwin [56] reported fluorescence-associated molecular biomarkers in preclinical and clinical assessments. Numerous fluorescently tagged antibodies, peptides, particles, and other compounds relevant to cancer hallmarks have been produced for the lighting of the target lesion, as underlined by Mieog [57], Privitera [58], Nagaya [59] and Tipirneni [60].…”
Section: Improving the Detection Of Cancer Tissue And Targeted Treatmentmentioning
confidence: 99%
“…A study by Lwin [44] describes molecular biomarkers associated with fluorescence in pre-clinical and clinical evaluation. For the illumination of target lesions, an impressive number of fluorescently labeled antibodies, peptides, particles, and other molecules related to cancer hallmarks have been developed, as shown by Mieog [45] , Privitera [46], Nagaya [47] and Tipirneni [48] .…”
Section: To Improve Detection Of Cancer Tissue and Target Treatmentmentioning
confidence: 99%
“…[1][2][3][4] As a treatment for cancer, surgery requires preoperative imaging to determine tumor boundaries, which may pose certain challenges to traditional localization methods due to scarring and brosis, which can mask viable tumors. 5 The high selectivity and sensitivity coupled with low trauma and cost of the emerging uorescent probe technology make it expected to be a reliable tool to solve the problem of cancer diagnosis and provide certain assistance in the clinical operation process. [6][7][8][9] The probe structure is divided into uorophore, linker, and recognition group.…”
Section: Introductionmentioning
confidence: 99%